2016
DOI: 10.1017/ice.2015.341
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fidelity in Interventions to Improve Hand Hygiene of Healthcare Workers: A Systematic Review

Abstract: OBJECTIVE Compliance with hand hygiene in healthcare workers is fundamental to infection prevention yet remains a challenge to sustain. We examined fidelity reporting in interventions to improve hand hygiene compliance, and we assessed 5 measures of intervention fidelity: (1) adherence, (2) exposure or dose, (3) quality of intervention delivery, (4) participant responsiveness, and (5) program differentiation. DESIGN Systematic review METHODS A librarian performed searches of the literature in PubMed, Cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 120 publications
0
6
0
2
Order By: Relevance
“…For example, lack of compliance with hand hygiene practices is a well-known issue for health care workers. 36 We found that birth attendants would wash hands if a coach was physically present, but when a coach was not present birth attendants performed hand hygiene on only 36% of occasions before delivery. Although hand hygiene is critical for infection prevention, 37 symptoms generally do not occur until after a mother and baby have been discharged from the facility and no longer are receiving care from the birth attendants.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, lack of compliance with hand hygiene practices is a well-known issue for health care workers. 36 We found that birth attendants would wash hands if a coach was physically present, but when a coach was not present birth attendants performed hand hygiene on only 36% of occasions before delivery. Although hand hygiene is critical for infection prevention, 37 symptoms generally do not occur until after a mother and baby have been discharged from the facility and no longer are receiving care from the birth attendants.…”
Section: Discussionmentioning
confidence: 74%
“…For example, lack of compliance with hand hygiene practices is a well-known issue for health care workers 36 . We found that birth attendants would wash hands if a coach was physically present, but when a coach was not present birth attendants performed hand hygiene on only 36% of occasions before delivery.…”
Section: Discussionmentioning
confidence: 80%
“…For the hand hygiene improvement project, we referred to the five descriptive factors for the systematic evaluation of interventional measures to formulate the implementation plan. Ensuring fidelity is crucial because it allows for the replication, evaluation, comparison, and dissemination of interventions (16)(17)(18). Implementation fidelity of an intervention has five domains: (I) adherence to the program; (II) exposure or dose (i.e., the proportion of the programme delivered); (III) quality of intervention delivery; (IV) participant responsiveness; and (V) program differentiation (i.e., the presence of distinguishing features of the intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare staff, may be colonized with microorganisms identified as causative agents in hospital infections as a result of contact with patients and patient surroundings 3,4. Healthcare-associated infections are preventable complications in inpatients, and preventive measures are recommended as one of the most effective strategies to prevent infections 5. Many outbreaks in hospitals are usually associated with poor levels of compliance with hand hygiene 4,6.…”
Section: Introductionmentioning
confidence: 99%